#TITLE_ALTERNATIVE# - FIRANDA (NIM 12204021); Pembimbing : Dr. Ir. Taufan Marhaendrajana, ERIC
Coalbed methane (CBM) is unconventional gas reservoir from coal. In early time, gas is adsorbed on coal surface in micropore. Caused by effect of pressure and temperature. When reservoir pressure is decreased, adsorbed gas will be released from coal surface, this process called desorption. Desorbed gas will flow as long as micropore to fracture (cleat) with diffusion process which effect of gas concentration gradient. In cleat, gas will flow according to convection (Darcian flow). Besides gas, it also have water which full up cleat. Early water saturation almost 100% then decrease while gas content is increasing to cleat. Gas flow in coalbed methane can be modeled start from desorbed gas on coal surface, flowing along micropore to cleat until gas flow along cleat to well bore thus production performance can be predicted. In this paper, author predicted gas production profile used manual calculation method (semi analytical) and the result is compared with simulator result which used numerical method.